Blood Pressure-Associated Genetic Variants in the Natriuretic Peptide Receptor 1 Gene Modulate Guanylate Cyclase Activity. (August 2019) - Vandenwijngaert, Sara; Ledsky, Clara D.; Lahrouchi, Najim; Khan, Mohsin A.F.; Wunderer, Florian; Ames, Lisa; Honda, Toshiyuki; Diener, John L.; Bezzina, Connie R.; Buys, Emmanuel S.; Bloch, Donald B.; Newton-Cheh, Christopher
Abstract : Background: Human genetic variation in the NPR1 (natriuretic peptide receptor 1 gene, encoding NPR-A, atrial natriuretic peptide receptor 1) was recently shown to affect blood pressure (BP). NPR-A catalyzes the intracellular conversion of guanosine triphosphate to cGMP (cyclic 3′, 5′-guanosine monophosphate) on binding of ANP, BNP (atrial or brain natriuretic peptide). Increased levels of cGMP decrease BP by inducing natriuresis, diuresis, and vasodilation. Methods: We performed a meta-analysis of low-frequency and rare NPR1 variants for BP association in up to 491 584 unrelated individuals. To examine whether the identified BP-associated variants affect NPR-A function, the cGMP response to ANP and BNP was measured in cells expressing wild-type NPR1 and cells expressing the NPR1 variants. Results: In this study, we identified BP associations of 3 amino acid altering variants of NPR1 . The minor alleles of rs35479618 (p.E967K, gnomAD non-Finnish European allele frequency 0.017) and rs116245325 (p.L1034F, allele frequency 0.0007) were associated with higher BP ( P =4.0×10 −25 and P =9.9×10 −8, respectively), while the minor allele of rs61757359 (p.G541S, allele frequency 0.003) was associated with lower BP ( P =1.8×10 −9 ). Cells transiently expressing 967K or 1034F NPR-A displayed decreased cGMP production in response to ANP and BNP (all P <10 –6 ), while cells expressing 541S NPR-A produced more cGMP compared with cells expressing wild-type NPR-A ( P ⩽4.13×10 −5 for ANP and P ⩽4.24×10 −3 for BNP). Conclusions: In summary, the loss or gain of guanylate cyclase activity for these NPR1 allelic variants could explain the higher or lower BP observed for carriers in large population-based studies. Abstract : Supplemental Digital Content is available in the text.